Jurisdiction Over Grave Breaches of Human Rights in Iraq Committed by (PMSCs) Contracted with the USA : The Nisur Square Incident - Altamimi, Hayder Ajeel Fadhil (Pravni zapisi, 2013)
This article examines and analyzes the available legal options to the jurisdiction over grave breaches of human rights suffered by Iraqi civilians at the hands of the personnel of private military and security companies contracted with the U.S. armed forces in Iraq,with reference to the incident of the killing of 17 Iraqi civilians and wounding others in the Nisur Square in Baghdad in 2007 as a result of shooting by Blackwater company personnel. During its direct administration to Iraq as an occupying power the United States have granted to members of its armed forces and contractors immunity from jurisdiction of Iraqi laws. Such immunity helped to some degree, to commit serious violations of human rights against Iraqi civilians and rendered the litigation or prosecution of perpetrators complex, given that the local remedies must be exhausted before searching the possibility of jurisdiction at the international level. Key words: Human Rights, Civilians, Jurisdiction, Nisur Incident.
Keywords: Human Rights; Civilians; Jurisdiction; Nisur Incident.